Crack-inclusion interaction in composite materials with aerospace and offshore engineering application - Koh, Way Keat (2018)
With the advancement in material technology, the use fiber reinforced composite materials have gained wide recognition and are currently utilized for various application. Example of such applications are in aerospace and offshore industry. This report aimed to explore the uses of composite material in these two applications and also to study the fracture mechanics of these complex material. Numerical method was used to acquire the stress intensity factor (SIF) of various model of crack near a circular inclusion by means of finite element software. Stress intensity factor data were collected by perturbing the crack with a uniform load. Parametric approach was used with different crack models to obtain various results of stress intensity factor. This was able to be achieved by introducing certain constant variables and a few sets of manipulating variables. Two types of crack were being modeled and analyzed, which were a straight crack (with coated and uncoated inclusion) and a symmetrical branch crack at one end (with uncoated inclusion). The outcome of the numerical analysis suggested that the presence of reinforced fiber (inclusion) in a material was able to reduce the stress intensity factor. However, the case was only shown to be true when the inclusion has a higher Young’s modulus compared to the matrix material. With lower stress intensity factor, this results to a higher resistance towards crack propagation and ultimately material failure.